2020
DOI: 10.1002/acr2.11204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID‐19 Pandemic on Patients Living With Vasculitis

Abstract: Objective This study aimed to analyze the concerns and health‐related behaviors in patients with vasculitis during the early phase of the coronavirus disease 2019 (COVID‐19) pandemic in North America. Methods Patients with vasculitis in North America were invited to complete an online survey through the Vasculitis Patient‐Powered Research Network in collaboration with the Vasculitis Foundation and the Relapsing Polychondritis Foundation. Questions focused on concerns and behaviors related to doctors’ visits, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 16 publications
4
24
0
2
Order By: Relevance
“…We found that 10% of patients receiving immunomodulatory medications had stopped one of their medications because of concerns about COVID‐19, even if they were well with no COVID‐19 diagnosis or respiratory illness. Most medication interruptions were not recommended by a physician, similar to results from previous studies (10–12,22,23). Guidance from the American College of Rheumatology recommends not stopping medications unless patients have contracted or been exposed to severe acute respiratory syndrome coronavirus 2, although this guidance was first published in April 2020 and was not available when many patients answered their surveys (24).…”
Section: Discussionsupporting
confidence: 85%
“…We found that 10% of patients receiving immunomodulatory medications had stopped one of their medications because of concerns about COVID‐19, even if they were well with no COVID‐19 diagnosis or respiratory illness. Most medication interruptions were not recommended by a physician, similar to results from previous studies (10–12,22,23). Guidance from the American College of Rheumatology recommends not stopping medications unless patients have contracted or been exposed to severe acute respiratory syndrome coronavirus 2, although this guidance was first published in April 2020 and was not available when many patients answered their surveys (24).…”
Section: Discussionsupporting
confidence: 85%
“…Information on outcome (i.e. relapses) was not part of the survey [ 42 ]. The first wave of the pandemic had a significant impact on patient care.…”
Section: Covid-19 and Anca-associated Vasculitismentioning
confidence: 99%
“…Telehealth use in rheumatology prior to the COVID-19 pandemic was primarily limited to treating patients in rural areas that were medically underserved (1,2). The COVID-19 pandemic, however, has led to substantial health care disruptions and a rapid rise in telehealth use among patients with rheumatic and musculoskeletal diseases (RMDs) (3)(4)(5)(6). Many of these patients are at increased risk of infection and may be at increased risk of severe COVID-19 due to immune dysregulation from their rheumatic condition, immunosuppressive medications, or multiple comorbid health conditions (i.e., multimorbidity) (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%